The Legal Position of Amicus Curiae's Opinion on Criminal Judicial Processes in Indonesia - Krisnalita, Louisa Yesami; Mutiarany, Mutiarany; Sharon, Grace; Mohamad, Ani Munirah (Universitas Muhammadiyah Surabaya, 2022)
Amicus curiae comes from the Latin